The Characteristic of Sound Reflections from Curved Reflective Panels - Agata SZELĄG; Mirosława LEWIŃSKA; Tadeusz Marek KAMISIŃSKI; Jarosław RUBACHA; Adam PILCH (Archives of Acoustics)
The paper presents the verification of a solution to the narrow sound frequency range problem of flat reflective panels. The analytical, numerical and experimental studies concerned flat panels, panels with curved edges and also semicircular elements. There were compared the characteristics of sound reflected from the studied elements in order to verify which panel will provide effective sound reflection and also scattering in the required band of higher frequencies, i.e. above the upper limit frequency. Based on the conducted analyzes, it was found that among some presented solutions to narrow sound frequency range problem, the array composed of panels with curved edges is the most preferred one. Nevertheless, its reflection characteristic does not meet all of the requirements, therefore, it is necessary to search for another solution of canopy which is effective over a wide frequency range.